Effects of Herpud1 in Methamphetamine-induced Neuronal Apoptosis - Lu, Shuang; Li, Yan; Wang, Lewen; Xiong, Kun; Yan, Jie; Zhai, Zhihao; Yan, Weitao (Current Medicinal Chemistry, 2025)
IntroductionMethamphetamine (METH) is an illicit psychoactive substance that can damage various organs in the body, especially the nervous system. We hypothesized that expression of homocysteine-inducible endoplasmic reticulum-resident with ubiquitin-like domain member 1 (Herpud1) protein would alleviate the induction of apoptosis following METH administration.MethodsTo test this hypothesis, we analysed the changes in Herpud1 expression and apoptosis in PC12 cells under different concentrations and exposure times of METH. Moreover, we examined the effects of Herpud1 knockdown on METH-induced neuronal apoptosis. Flow cytometry and Western blot analyses were used to evaluate apoptosis levels and the expression of apoptotic markers (cleaved caspase-3) in PC12 cells following Herpud1 knockdown by synthetic small interfering RNA (siRNA).ResultsOur results showed that Herpud1 expression was upregulated in PC12 cells following METH treatment, while endoplasmic reticulum stress (ERS) and apoptosis were also increased. Conversely, Herpud1 knockdown reduced METH-induced ERS and apoptosis levels in vitro.ConclusionThese results suggest that Herpud1 plays an essential role in METH-induced neuronal ERS and apoptosis and may represent a potential therapeutic gene target in METH-induced neurotoxicity.
Keywords: neurotoxicity